Low energy sputtering of Mo surfaces - Granberg, F.; Litnovsky, A.; Nordlund, K. (Journal of nuclear materials, 2020)
Surfaces of materials subject to irradiation will be affected by sputtering, which can be a beneficial effect, like in the coating industry where a material is sputtered and redeposited on to another material to coat it. However, in most cases sputtering is an unwanted side-effect, for instance in nuclear fusion reactors, where the wall material will be degraded. This effect needs to be understood in order to be able to predict its consequences. To understand the sputtering, on an atomistic level, we have thoroughly investigated molybdenum surface sputtering by computational means. Molybdenum was chosen as detailed experimental studies have been carried out on it and it is one candidate material for the diagnostic mirrors in ITER, facing the plasma. In this study, we thoroughly investigate the molybdenum samples of different surface orientations, and their response to low energy argon plasma irradiation, by molecular dynamics simulations. We find both a surface orientation and ion energy specific sputtering yield of the samples, and a very good agreement with the experiments available in the literature. A few different setups were investigated to observe differences as well as to understand the key features affecting the sputtering events. The different simulation setups revealed the optimal one to represent the experimental conditions as well as the mechanisms behind the observed discrepancies between different modelling setups.